High-selectivity etching liquid for radio frequency chip material

By using a high selective etching solution containing alkaline substances, oxidants, corrosion inhibitors and stabilizers during the etching process of RF chip materials, the problem of high selectivity ratio etching of scandium-doped aluminum nitride layer and damage to the tungsten layer is solved. Achieve high selection ratio etching and low damage effects.

CN119432383AActive Publication Date: 2025-02-14HUBEI SINOPHORUS ELECTRONIC MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411343819.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-14
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

During the etching of RF chip materials, it is difficult for the prior art to reduce the damage of the tungsten layer while maintaining a high selectivity ratio etching of the scandium doped aluminum nitride layer.

Method used

Using a highly selective etching liquid containing alkaline substances, oxidants, corrosion inhibitors and stabilizers, the etching rate and uniformity of the etching liquid are adjusted to achieve scandium doping by adding corrosion inhibitors and stabilizers to the system. High selectivity ratio etching of aluminum nitride to tungsten.

Benefits of technology

A high selective ratio etching of scandium-doped aluminum nitride and tungsten (the selection ratio reaches more than 900) was achieved, and the number of damage in the tungsten layer was significantly reduced, with the damage accounting for less than 1%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432383A_ABST
    Figure CN119432383A_ABST
Patent Text Reader

Abstract

The invention discloses a high-selectivity etching solution for a radio frequency chip material. The etching solution comprises 15 # imgabs0 # alkaline substance with the mass content of 20%; 0.1 # imgabs1 # an oxidant with a mass content of 0.25%; 0.1 # imgabs2 #, and a corrosion inhibitor with the mass content of 0.2%; the mass content of the stabilizer is 0.05%, and the mass content of the stabilizer is 0.01 # imgabs3 #; and the balance of deionized water. According to the etching solution for the high-selectivity radio frequency chip material, high-selectivity etching of scandium-doped aluminum nitride and metal tungsten in the chip material can be realized, and etching of the metal tungsten is avoided to the greatest extent while complete etching of the scandium-doped aluminum nitride is ensured; and the number of damages caused by the etching liquid to the tungsten layer can be greatly reduced by adding the stabilizer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electronic chemicals, and in particular relates to a highly selective etching solution for radio frequency chip materials. Background Art

[0002] The development of modern military electronic equipment and civilian communication systems has put forward the requirements of miniaturization, multi-function and reconfigurability for RF systems, and the functional complexity of RF systems is increasing. At present, various data indicators of RF chips are being continuously optimized, and their frequency coverage has reached the microwave and terahertz bands. In 5G communication technology, a large number of medium and high frequency devices are required, mainly including filters, power amplifiers, low noise amplifiers, RF switches, etc. Compound semiconductor materials are the core key materials for the preparation of these devices. Scandium-doped aluminum nitride (ScAlN) as a piezoelectric film material has significant advantages such as high sound velocity, good thermal stability, wide band gap, and especially compatibility with CMOS process. At the same time, it can overcome the shortcomings of aluminum nitride (AlN) piezoelectric film, such as small piezoelectric coefficient and low electromechanical coupling coefficient. The performance of ScAlN film determines the quality of RF chips to a certain extent. When ScAlN is combined with different metals to form RF chip materials, its performance will also be improved to varying degrees. After combining with different film layers, it is necessary to obtain the specific pattern required by the process through further etching. Summary of the invention

[0003] The present invention aims to provide a high-selectivity etching solution for radio frequency chip materials, which can reduce the damage amount of tungsten layer while maintaining high selectivity for etching scandium-doped aluminum nitride layer.

[0004] The present invention relates to a highly selective etching solution for radio frequency chip materials, wherein the etching solution comprises an alkaline substance, an oxidant, a corrosion inhibitor, a stabilizer and deionized water. 20%; oxidant mass content is 0.1 0.25%; the mass content of corrosion inhibitor is 0.1 0.2%; the mass content of stabilizer is 0.01 0.05%; the rest is deionized water.

[0005] In the etching solution of the present invention, the main alkaline substance is one or a combination of potassium hydroxide, sodium hydroxide, ammonia water, tetramethylammonium hydroxide and tetraethylammonium hydroxide.

[0006] In the etching solution of the present invention, the oxidant comprises one or a combination of ammonium persulfate, potassium persulfate, sodium hypochlorite, potassium iodide and catechol.

[0007] The main function of the oxidant is to increase the etching rate of the scandium-doped aluminum nitride, thereby improving the etching selectivity of the scandium-doped aluminum nitride and the tungsten layer.

[0008] Adding an oxidant to the alkaline formula can accelerate the etching rate of the ScAlN layer, but when a certain amount of oxidant exists in the system, the etching rate of the tungsten layer is also significantly accelerated, causing varying degrees of damage to the tungsten layer. Therefore, it is necessary to reduce the etching rate of the tungsten by the etching solution by adding a corrosion inhibitor. On the other hand, the damage is closely related to the etching uniformity of the etching solution. A good stabilizer can increase the etching uniformity of the system, thereby reducing the amount of damage to the tungsten layer.

[0009] In the etching solution of the present invention, the corrosion inhibitor includes one or a combination of imidazole, 2-propyl imidazole, 2-undecyl imidazole, 3-mercapto-1,2,4-triazole, benzotriazole, methylbenzotriazole, 1,2,3-triazole, polyethyleneimine, quinoline-4-amine, and 4-quinolinemethanol.

[0010] Tungsten corrosion inhibitor selectively combines with the surface of metal tungsten to specifically reduce the etching rate of the tungsten layer and achieve high selectivity etching.

[0011] In the etching solution of the present invention, the stabilizer includes one or a combination of 4-(methylamino)butyl tert-butyl carbamate, 2-(methylamino)propyl tert-butyl carbamate, tert-butyl carbamate, tert-butyl 8-aminooctanoate, tert-butyl morpholine-3-methylcarbamate, tert-butyl (2-amino-tert-butyl) carbamate, trimethylsilyl valerolactam, 5-tert-butyl azepan-2-one, 2-amino-δ-valerolactam, and (S)-3-amino-2-caprolactam.

[0012] The advantages of the present invention are: compared with the prior art, the present invention provides a highly selective etching solution for radio frequency chip materials, the etching selectivity ratio of scandium-doped aluminum nitride to tungsten in the chip material can reach more than 900, and through structural surface analysis, the amount of damage to the tungsten layer is greatly reduced.

[0013] (1) The etching solution of the present invention significantly improves the etching rate of scandium-doped aluminum nitride in the presence of an oxidant.

[0014] (2) The etching solution of the present invention achieves high selective etching of scandium-doped aluminum nitride and tungsten by adding a corrosion inhibitor to the system. The selectivity can reach more than 900, and the tungsten etching rate is less than 10.7 Å / min.

[0015] (3) The stabilizer in the etching solution of the present invention prevents part of the etching solution from etching too fast in the longitudinal direction, penetrating the scandium-doped aluminum nitride layer, reaching the tungsten layer and causing damage to the tungsten layer, and the damage ratio is less than 1%. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1This is an ultra-depth-of-field microscope image of etching scandium-doped aluminum nitride and tungsten structure wafers in Comparative Example 1; Figure 2 This is an ultra-depth-of-field microscope image of etching scandium-doped aluminum nitride and tungsten structure wafers in Comparative Example 2; Figure 3 This is an ultra-depth-of-field microscope image of etching the scandium-doped aluminum nitride and tungsten structure sheet in Example 3; Figure 4 This is an ultra-depth-of-field microscope image of etching the scandium-doped aluminum nitride and tungsten structure sheet in Example 7. DETAILED DESCRIPTION

[0017] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. The embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.

[0018] Example 1 In the embodiment 1, 0.15% by mass of imidazole is added as a tungsten etching inhibitor, and 0.01% by mass of 4-(methylamino)butylcarbamate is added as a stabilizer, specifically as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, the mass content of imidazole is 0.15%, the mass content of tert-butyl 4-(methylamino)butylcarbamate is 0.01%, and the balance is water.

[0019] The etching solution prepared according to the above ratio was used to etch the scandium-doped aluminum nitride single wafer on the silicon substrate at 55°C (the scandium-doped aluminum nitride wafer was cut into regular squares of 2*2 cm in size). In order to avoid inaccurate measurement caused by the hydrolysis of scandium aluminum nitride in the air, the scandium aluminum nitride wafer was first cleaned in a low-concentration alkali solution (2% ammonia water) for 10 seconds to remove the hydrolyzed oxide layer on the surface. The scandium aluminum nitride wafer was measured using an ellipsometer spectropolarimeter, and the initial thickness of the scandium-doped aluminum nitride was calculated by model fitting. The average value of 4 points of the single wafer was taken. Then the scandium aluminum nitride wafer was placed in the etching solution for 10 seconds, cleaned and dried with nitrogen, and the aluminum nitride spectrum was tested using an ellipsometer (keeping the test points consistent before etching). The scandium aluminum nitride thickness was obtained by fitting calculation and taking the average value, and the scandium aluminum nitride etching rate was calculated. The etching rate of the scandium aluminum nitride wafer can reach 15.96 nm / s by the etching solution configured in the above proportion.

[0020] The etching solution configured according to the above ratio was used to etch the metal tungsten on the silicon substrate at 55°C (the tungsten sheet was cut into regular squares of 2*2 cm in size). In order to avoid inaccurate measurement due to oxidation of the tungsten sheet in the natural environment, the tungsten sheet was first cleaned in a low-concentration acid solution (2% HF) for 10 s to remove the oxide layer, and then the resistance of the tungsten sheet was measured using a four-probe resistance meter. The initial thickness was calculated, and the average value of 4 points was measured for a single sheet. The tungsten sheet was then placed in the etching solution for 600 s, cleaned and dried with nitrogen, and the four-probe measurement of the tungsten sheet resistance (the measurement points were consistent before and after etching) obtained the thickness of the tungsten sheet, and the tungsten sheet etching rate was calculated. The etching rate of the tungsten sheet can reach 10.32 Å / min using the etching solution configured in the above ratio.

[0021] At the same time, 50 g of etching solution was used to etch a 2*2 cm scandium-doped aluminum nitride and tungsten structure sheet, and the amount of damage to the tungsten layer was detected and counted using an ultra-depth of field microscope. The amount of etching damage in this embodiment was 4 / 607, and the proportion of damage to the tungsten layer was less than 1%.

[0022] It can be seen that the etching selectivity of the above formula for scandium-doped aluminum nitride and metal tungsten is 927.91, the amount of etching damage is 4 / 607, and the damage to the tungsten layer accounts for less than 1%.

[0023] The etching rates, damage amounts and damage ratios of the subsequent embodiments and comparative examples are shown in Table 1.

[0024] Example 2 In the embodiment 2, 0.15% by mass of imidazole is added as a tungsten etching inhibitor, and 0.01% by mass of 4-(methylamino)butylcarbamate is added as a stabilizer, specifically as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, the mass content of imidazole is 0.15%, the mass content of tert-butyl 4-(methylamino)butylcarbamate is 0.01%, and the balance is water.

[0025] Example 3 In the embodiment 3, 0.15% by mass of 2-propyl imidazole is added as a tungsten etching inhibitor, and 0.01% by mass of 4-(methylamino)butyl tert-butyl carbamate is added as a stabilizer, as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, the mass content of 2-propylimidazole is 0.15%, the mass content of tert-butyl 4-(methylamino)butylcarbamate is 0.01%, and the balance is water.

[0026] Example 4 In the embodiment 4, 0.15% by mass of 1,2,3-triazole is added as a tungsten etching inhibitor, and 0.01% by mass of 4-(methylamino)butylcarbamic acid tert-butyl ester is added as a stabilizer, as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, the mass content of 1,2,3-triazole is 0.15%, the mass content of tert-butyl 4-(methylamino)butylcarbamate is 0.01%, and the balance is water.

[0027] Example 5 In the embodiment 5, 0.15% by mass of benzotriazole is added as a tungsten etching inhibitor, and 0.01% by mass of 4-(methylamino)butylcarbamate is added as a stabilizer, specifically as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, the mass content of benzotriazole is 0.15%, the mass content of tert-butyl 4-(methylamino)butylcarbamate is 0.01%, and the balance is water.

[0028] Example 6 In the embodiment 6, 0.15% by mass of quinoline-4-amine is added as a tungsten etching inhibitor, and 0.01% by mass of 4-(methylamino)butylcarbamic acid tert-butyl ester is added as a stabilizer, as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, the mass content of quinoline-4-amine is 0.15%, the mass content of tert-butyl 4-(methylamino)butylcarbamate is 0.01%, and the balance is water.

[0029] Example 7 In the embodiment 7, 0.15% by mass of polyethyleneimine is added as a tungsten etching inhibitor, and 0.01% by mass of 4-(methylamino)butylcarbamate is added as a stabilizer, specifically as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, the mass content of polyethyleneimine is 0.15%, the mass content of tert-butyl 4-(methylamino)butylcarbamate is 0.01%, and the balance is water.

[0030] Example 8 In the embodiment 8, 0.15% by mass of 2-propyl imidazole is added as a tungsten etching inhibitor, and 0.01% by mass of tert-butyl carbamate is added as a stabilizer, specifically as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, the mass content of 2-propylimidazole is 0.15%, the mass content of tert-butyl carbamate is 0.01%, and the balance is water.

[0031] Example 9 In the embodiment 9, 0.15% by mass of 2-propyl imidazole is added as a tungsten etching inhibitor, and 0.01% by mass of (2-amino-tert-butyl) tert-butyl carbamate is added as a stabilizer, specifically as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, the mass content of 2-propylimidazole is 0.15%, the mass content of (2-amino-tert-butyl)carbamate is 0.01%, and the balance is water.

[0032] Example 10 In the embodiment 10, 0.15% by mass of 2-propyl imidazole is added as a tungsten etching inhibitor, and 0.01% by mass of trimethylsilyl valerolactam is added as a stabilizer, specifically as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, the mass content of 2-propylimidazole is 0.15%, the mass content of trimethylsilylvalerolactam is 0.01%, and the balance is water.

[0033] Embodiment 11 The embodiment 11 adds 0.15% by mass of 2-propyl imidazole as a tungsten etching inhibitor and 0.01% by mass of 5-tert-butyl azepan-2-one as a stabilizer, specifically as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, the mass content of 2-propylimidazole is 0.15%, the mass content of 5-tert-butylazepan-2-one is 0.01%, and the balance is water.

[0034] Example 12 In the embodiment 12, 0.15% by mass of 2-propyl imidazole is added as a tungsten etching inhibitor, and 0.01% by mass of (S)-3-amino-2-caprolactam is added as a stabilizer, specifically as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, the mass content of 2-propylimidazole is 0.15%, the mass content of (S)-3-amino-2-caprolactam is 0.01%, and the balance is water.

[0035] Comparative Example 1 Based on Example 1, the difference is that Comparative Example 1 is an etching solution without adding tungsten etching inhibitor and stabilizer, which is as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, and the rest is deionized water.

[0036] Comparative Example 2 Based on Example 1, the difference is that Comparative Example 2 does not add a stabilizer, and the details are as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, the mass content of imidazole is 0.15%, and the balance is water.

[0037] Comparative Example 3 Based on Example 1, the difference is that Comparative Example 3 does not add a corrosion inhibitor, and the details are as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, the mass content of tert-butyl 4-(methylamino)butylcarbamate is 0.01%, and the rest is deionized water. Comparative Example 4 Based on Example 1, the difference is that Comparative Example 4 adds other types of corrosion inhibitors, which are as follows: The mass content of potassium hydroxide is 20%, the mass content of ammonium persulfate is 0.2%, the mass content of ethylenediaminetetramethylenephosphonic acid is 0.15%, the mass content of tert-butyl 4-(methylamino)butylcarbamate is 0.01%, and the rest is deionized water. By comparing the data in Table 1 with Example 1 and Comparative Example 2, it can be clearly found that the corrosion inhibitor has a significant corrosion inhibition effect on the etching of the tungsten layer, and the etching rate of tungsten is reduced from 375 Å / min to 9.53 Å / min. Figure 2 and Figure 3 It can be found that after adding the stabilizer, the amount of damage to the tungsten layer is significantly reduced. Through the experimental results of Example 1 and Comparative Example 3, it can be found that adding only a stabilizer can neither increase the selectivity nor reduce the amount of damage to the tungsten layer. Through the experimental results of Comparative Example 4, it can be found that other types of corrosion inhibitors (phosphonic acids) combined with stabilizers cannot reduce the amount of damage to the tungsten layer. Comparing Examples 1-6, it can be found that there are certain differences in the corrosion inhibition effects of corrosion inhibitors of different structures on the tungsten layer, but under the joint action of the stabilizer and the corrosion inhibitor, the amount of damage to the tungsten layer is greatly reduced. Under the same conditions, the tungsten layer of Example 3 has the best corrosion inhibition effect, the selectivity can reach 1346.48, and the number of damages is 5 / 612, and the damage ratio is 0.82%, which is significantly improved compared to Comparative Examples 1-4. Examples 7-12 mainly compare the improvement effects of different stabilizers on the amount of damage to the tungsten layer. Example 7 not only achieves high selective etching of scandium-doped aluminum nitride and tungsten (selectivity ratio greater than 1303), but also achieves the purpose of protecting the tungsten layer, reducing the amount of damage to the tungsten layer to 2 / 623, and the damage ratio is 0.32%.

[0038] Table 1 Data and selectivity of etching experiments of embodiments and comparative examples

[0039] The technical solution of the present invention is explained through the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above specific embodiments to be implemented. Any improvements made by technicians in the relevant field based on the present invention, or equivalent replacement of the materials selected by the present invention, etc., fall within the scope of protection of the patent.

Claims

1. A highly selective etching solution for radio frequency chip materials, characterized in that: The highly selective etching solution for radio frequency chip materials comprises the following raw material components: 15 20% by mass of alkaline substances; 0.1 0.25% by mass of oxidant; 0.1 0.2% by mass content of corrosion inhibitor; 0.01 0.05% by mass of stabilizer; The balance was deionized water.

2. The highly selective etching solution for radio frequency chip materials according to claim 1, characterized in that: The alkaline substance includes one or a combination of the main alkaline substances potassium hydroxide, sodium hydroxide, ammonia water, tetramethylammonium hydroxide and tetraethylammonium hydroxide.

3. The highly selective etching solution for radio frequency chip materials according to claim 1, characterized in that: The oxidant includes one or a combination of ammonium persulfate, potassium persulfate, sodium hypochlorite, potassium iodide, and catechol.

4. The highly selective etching solution for radio frequency chip materials according to claim 1, characterized in that: The corrosion inhibitor includes one or a combination of imidazole, 2-propyl imidazole, 2-undecyl imidazole, 3-mercapto-1,2,4-triazole, benzotriazole, methylbenzotriazole, 1,2,3-triazole, polyethyleneimine, quinoline-4-amine, and 4-quinolinemethanol.

5. The highly selective etching solution for radio frequency chip materials according to claim 1, characterized in that: The stabilizer includes one or a combination of tert-butyl 4-(methylamino)butylcarbamate, tert-butyl 2-(methylamino)propylcarbamate, tert-butyl carbamate, tert-butyl 8-aminooctanoate, tert-butyl morpholine-3-methylcarbamate, tert-butyl (2-amino-tert-butyl)carbamate, trimethylsilylvalerolactam, 5-tert-butylazepan-2-one, 2-amino-δ-valerolactam, and (S)-3-amino-2-caprolactam.

6. The highly selective etching solution for radio frequency chip materials according to claim 1, characterized in that: The etching selectivity ratio of scandium-doped aluminum nitride and metallic tungsten in the chip material is greater than 900, the etching rate of tungsten is less than 10.7 Å / min, there is no scandium-doped aluminum nitride residue, and the damage rate of the tungsten layer is less than 1%.

Citation Information

Patent Citations

  • Wet etching process method for high-selectivity scandium-doped aluminum nitride

    CN113991009A

  • Scandium-doped aluminum nitride and tungsten selective etching solution

    CN114989825A

  • Selective etching solution for aluminum nitride and tungsten

    CN115011347A

  • Aluminum nitride etching solution and application thereof

    CN115011348A

  • Scandium-doped aluminum nitride etching solution and application thereof

    CN115044376A